Evaluation of the potential feedstock for biojet fuel production: Focus in the Brazilian context - Escalante, Edwin Santiago Rios [UNESP]; Ramos, Luth Silva [UNESP]; Rodriguez Coronado, Christian J.; de Carvalho Júnior, João Andrade [UNESP] (Elsevier, 2022)
The Brazilian aviation sector aiming to reduce its greenhouse emissions up to 37% by 2030 and up to 43% by 2050 (compared to 2005) using alternative fuels. For this reason, the evaluation of potential feedstock was made for the biojet fuel production focused in the Brazilian context. Four biomass types were proposed (Sugarcane, Jatropha, Soybeans and Eucalyptus), considering three factors: feedstock abundance (without negative impact in population foods), advances in conversion technology, and blend limit already approved by the ASTM International for the use of biojet fuels into fossil jet fuel. Based on this study, it is concluded that Brazil has a great number of available lands for the culture of feedstock from which aviation alternative fuel can be produced, with possible substitution of up to 10% vol. Of fossil jet fuel consumed in the country. However, conversion technologies are still a challenge. Only, Synthetic Paraffinic Kerosene (SPK) obtained by both Fischer Tropsch (FT) process and Alcohol to Jet (ATJ) process offer competitive prices compared to petroleum-based jet fuel. Considering sugarcane as the main feedstock, a self-sustained integrated process was evaluated aiming to increase the production performance of biojet fuel. Four biojet fuels were obtained by this process (ATJ – SPK, FT – SPK, Farnesane and Hexanol), allowing the reduction of up to 19.16% in the number of cultivated lands for sugarcane and up to 56.12% for its forest residues. Finally, the payload versus range ratio was described using the Breguet range equation applied to a possible commercial flight, taking into account all biojet fuels produced from the proposed feedstock including their blends.
Keywords: Biojet fuels; Brazilian aviation; Farnesane; Jatropha; Oxygenated fuels; Sugarcane